Dating North Pacific Abyssal Sediments by Geomagnetic Paleointensity: Implications of Magnetization Carriers, Plio-Pleistocene Climate Change, and Benthic Redox Conditions - Wang, Wanzhang; von Dobeneck, Tilo; Frederichs, Thomas; Zhang, Yang; Lembke-Jene, Lester; Tiedemann, Ralf; Winklhofer, Michael; Nürnberg, Dirk (Frontiers in Earth Science, 2021)
Non-carbonaceous abyssal fine-grained sediments cover vast parts of the North Pacific’s deep oceanic basins and gain increasing interests as glacial carbon traps. They are, however, difficult to date at an orbital-scale temporal resolution and still rarely used for paleoceanographic reconstructions. Here, we show that sedimentary records of past geomagnetic field intensity have high potential to improve reversal-based magnetostratigraphic age models. Five sediment cores from Central North Pacific mid-latitudes (39-47°N) and abyssal water depths ranging from 3900 to 6100 m were cube-sampled at 23 mm resolution and analyzed by automated standard paleo- and rock magnetic methods, XRF scanning, and electron microscopy. Relative Paleointensity (RPI) records were determined by comparing natural versus anhysteretic remanent magnetization losses during alternating field demagnetization using a slope method within optimized coercivity windows. The paleomagnetic record delivered well interpretable geomagnetic reversal sequences back to 3 Ma. This age span covers the climate-induced transition from a biogenic magnetite prevalence in the Late Pliocene and Early Pleistocene to a dust-dominated detrital magnetic mineral assemblage since the Mid-Pleistocene. Volcaniclastic materials from concurrent eruptions and gravitational or contouritic sediment re-deposition along extinct seamount flanks provide a further important source of fine- to coarse-grained magnetic carriers. Surprisingly, higher proportions of biogenic versus detrital magnetite in the late Pliocene correlate with systematically lowered RPI values, which seems to be a consequence of magnetofossil oxidation rather than reductive depletion. Our abyssal RPI records match the astronomically tuned stack of the mostly bathyal Pacific RPI records. While a stratigraphic correlation of rock magnetic and element ratio logs with standard oxygen isotope records was sporadically possible, the RPI minima allowed to establish further stratigraphic tie points at ~50 kyr intervals. Thus, this RPI-enhanced magnetostratigraphy appears to be a major step forward to reliably date unaltered abyssal North Pacific sediments close to orbital-scale resolution.